Assessing the Adoption of a Home Health Provisioning System in India: an analysis of doctors' knowledge, attitudes and perceptions - Nikunj Agarwal; Nikunj Agarwal; MP Sebastian; Shikhar Agarwal (ACHSM, 2016)
Background: Unlike developed countries, home healthcare provision systems (HHPS) are not widely prevalent in developing countries like India. Our objective was to study the knowledge, attitudes and perceptions of doctors in India about the adoption of HHPS. Methods: Our survey included 180 doctors across India, working in local hospitals. Using online and paperbased questionnaires, we used bar charts and pie charts to represent the frequency distributions. We also conducted multivariate logistic regression analysis to understand the importance of the selected factors upon the dependent variables of interest such as willingness to work during non-office hours, desire for increased remuneration, and willingness to enrol in HHPS. Results: The desire for an increase in remuneration made doctors more willing to enrol in HHPS. Possible reasons for doctors to enrol included the ability to answer follow-up queries through email or video chat and HHPS being integrated with the local healthcare system in the hospital. Young male doctors were most likely willing to provide services through HHPS during nonoffice hours as compared to females. A large majority of doctors indicated hospital visits to be important for follow-up queries, but several doctors indicated that simple patient queries could be addressed by nonpersonal interactions like video chat or email. Conclusions: The desire for extra remuneration could be the primary reason for the willingness of doctors to work during non-office hours and thus enrol in HHPS. The majority of doctors considered hospital visits to be important, but several doctors also indicated that nonpersonal interactions using text messages, telephone, email and video chat might serve as important methods to respond to simple follow-up queries from patients. Abbreviations: EMR - Electronic Medical Record; HHPS - Home Help Provisioning Systems; ICT - Information and Communication Technology; ISO - International Organisation for Standardisation.